Manual Colaborativo das Secretarias Departamentais da UFES: Ferramenta Online de Suporte Administrativo - Oliveira, Afonso Henrique (2019)
Every organization has a purpose, objectives and goals, this set that will guide the application of the resources necessary to achieve them. The employees who make up these organizations must act within an organizational structure with predefined roles. Focusing on the activities performed at the operational level, this level comprises the administrative routines that are performed routinely and daily, in order to achieve these results. This study aims to study the development of administrative routines in the UFES departmental departments, in order to identify the main routines, the difficulties of the servers to execute them, and if they are in agreement with the university regiments and resolutions. More specifically through the use of an online knowledge management tool, the wiki, which allows the registration of administrative routines of university departmental departments as a collaborative manual. It was found that the administrative staff working in the departmental departments of UFES is relatively young, 70.2% of these servers are in the age group of 21 to 40 years old. This team is well qualified, with a large number of specialists and masters, 43.3% and 20.9% respectively, all have at least a college degree. In conclusion, this team has the necessary training and capacity to perform departmental routines. However, secretaries encounter difficulties in performing routines due to the lack of standardization of their activities and the lack of formal description of the execution of procedures. This study also found that unified departmental secretariats have less difficulty performing administrative routines than single departmental secretaries. The level of difficulty in the unified secretariats is concentrated in the low level, with 52.6%, while the level of single departments is concentrated in the median level, with 45.8%. This is due to the presence of a work team and guide in the unified secretariats. The online tool developed in this study fits perfectly in solving the difficulties encountered, acting in the process of creation, discussion, publication and dissemination of administrative routines of departments. This type of tool requires the contribution and participation of the population involved, and one of the factors that contributes to its construction of the wiki is the existence of servers that already perform, by their own initiative, the compilation of some kind of administrative routines. Almost half of the secretaries, 44.8%, reported that they make or know of a server in the secretariat that makes this kind of compilation. And 92.5% of the secretaries approved the idea of creating a website, containing the routines of departmental secretaries. And that 67.2% of the secretaries wish they could make suggestions and changes. The web application built in this research will contribute to the development of activities of departmental departments, assisting in the construction and sharing of administrative routines. In addition, the product of this research can be expanded to other sectors of the institution.